Can citizens say 'no'?: Tracking civil society's impact in Parliament - Mohamed, Nazeema; Kadalie, Bruce; Nyirongo, Rachael (New Agenda: SA Journal of Social and Economic Policy, 2025)
Active citizen involvement, a foundational element of South Africa's democratic framework, aims to ensure that all voices, especially those historically on the margins, are acknowledged and actively incorporated into policy decision-making. Yet this fine principle, clearly stipulated in the Constitution, encounters a fundamental contradiction when it comes up against the challenges of implementation.In reality, South Africa’s organised civil society today, itself the product of an powerful history of community-based resistance that overcame apartheid, is impeded from fulfilling this constitutional duty by severe shortages of capacity and resources. It is trapped in a tangle of bureaucratic inefficiencies, fragmented government coordination and limited public engagement and awareness.